(untitled) (Research, Society and Development, 2020)
Objective: To describe the profile and positioning of public-school teachers in relation to health education, emphasizing sexuality, seeking to investigate associations in this context. Methodology: It was an experimental cross-sectional descriptive study. Data collection occurred in a public school and the sample consists of 27 teachers, with an age average of 45.6 years (SD= 8.41). Results: Most of teachers have never taken an official course on sexual education, however, feel comfortable for discussions about sexuality. The majority of them mention that students have space for discussing the subject. Teachers who have taken and those who didn’t have sexual education courses have the same opinion in relation to the student having space to discuss sexuality and their feelings towards this dialogue. Most teachers reported that they address this theme with students on informal conversations. Conclusion: The participants of this research, mostly, presented post-graduate academic training. Regarding the profile of the sample, most reported acting for more than ten years in teaching. Regarding training courses on sexual education, most teachers have never performed them, however they feel comfortable for discussions about sexuality in their classes, regardless of the time of professional performance. Also, they believe that students have room for conversations on this subject during their classes, regardless of the discipline taught. Considering the perception of teachers, teenage pregnancy and contraceptive methods are the subjects most requested by students in relation to the sexuality theme.